Pengaruh Evaluasi Online Terhadap Hasil Belajar Mahasiswa Program Studi Pendidikan Agama Islam - Lismawati; Shobah Shofariyani Iryanti; Anisya Fitrah Amalia (Jurnal Pendidikan Islam, 2021)
This study aims to determine how much influence the evaluation of online learning using the Quizizz application and Google Form has on student learning outcomes within the scope of the Islamic Religious Education study program. This type of research is a quantitative research with a quasi-experimental research method. The data collection method was carried out using a test technique with a research design of pretest-posttest control group design, where the researcher gave a pretest with the aim of getting students' initial scores through the google form. The posttest was also given using the Quizizz application, then analyzed using data tabulation to draw conclusions. The place where the research was carried out was at FAI UHAMKA, South Jakarta. The samples used in this study were PAI VI A (Google form) and VI D (Quizizz). The data collected includes primary data. Primary data was obtained from the results of the pre-test and post-test of students. The results of the study confirm that there is an effect of online evaluation on the learning outcomes of PAI UHAMKA students in semester 6 of the Statistics course. This was obtained from the results of the study which showed that there was an increase from the original average value of 42.17 to 48.5.